2020
DOI: 10.3389/fsurg.2020.575318
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and New Technologies in Spine Surgery, Circa 2020: A Fifty-Year Review

Abstract: Spine surgery (lumbar, cervical, deformity, and entire spine) has increased in volume and improved in outcomes over the past 50 years because of innovations in surgical techniques and introduction of new technologies to improve patient care. Innovation is described as a process to add value or create change in an enterprise's economic or social potential. This mini review will assess two of three assessments of innovation in spine surgery: scientific publications and patents issued. The review of both scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This focus on innovation is crucial to academic spine surgery, which has seen an exponential increase in both innovative new surgical techniques and peer-reviewed publications between the years of 1970 and 2019, with 65.1% of publications occurring since 2006. 20 Yet, the divergence between what appears to be the respondents' intent and the ultimate hiring outcome merits speculation. It is possible that in-house hiring is not premeditated to maintain a “lineage” as much as it is the product of the stronger initial relationship between the hiring faculty and the new hire.…”
Section: Discussionmentioning
confidence: 99%
“…This focus on innovation is crucial to academic spine surgery, which has seen an exponential increase in both innovative new surgical techniques and peer-reviewed publications between the years of 1970 and 2019, with 65.1% of publications occurring since 2006. 20 Yet, the divergence between what appears to be the respondents' intent and the ultimate hiring outcome merits speculation. It is possible that in-house hiring is not premeditated to maintain a “lineage” as much as it is the product of the stronger initial relationship between the hiring faculty and the new hire.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to consider that the reason these studies are highly cited may perhaps be due to the excitement that surrounds the dynamic interplay between advancements in the industry and the pioneers of spinal surgery. Indeed, the arena for discussing these innovations has been rapidly expanding with a 50-year review finding that out of 1,162 publications found with the search terms 'innovation', 'new technology', and 'spine surgery', 83% were published after 2006 (15). These technologies are unique, ranging from 3D-printed prosthesis and drill guides, surgical navigation, robot-assisted surgeries, and sensor-based 'wearables'.…”
Section: Discussionmentioning
confidence: 99%